Angiogenesis and anti-angiogenic therapy in gastric cancer - Nienhüser, Henrik; Schmidt, Thomas (International journal of molecular sciences, 2018)
Gastric cancer is one of the most frequent malignancies worldwide. Despite improvements in diagnosis and therapy, the overall prognosis remains poor. In the last decade, several anti-angiogenic drugs for cancer treatment have been approved and lately also introduced to gastric cancer treatment. While the initial trials focused only on unresectable or metastatic cancer, anti-angiogenic treatment is now also investigated in the perioperative and neoadjuvant setting. In this review, an overview of the role of angiogenesis and angiogenic factors in gastric cancer as well as anti-angiogenic treatment of gastric cancer is provided. Findings from in vitro and animal studies are summarized and put in a context with translational data on angiogenesis in gastric cancer. The most important angiogenic factors and their effect in gastric cancer are highlighted and clinical trials including anti-angiogenic drugs are discussed. Finally, an outlook of biomarkers for predicting response to anti-angiogenic treatment is presented, the ongoing trials on this topic are discussed and current challenges of anti-angiogenic therapy are outlined.